2023
DOI: 10.1021/acs.joc.2c02584
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Methylene Insertion between Amines and Terminal Alkynes via C–N Bond Cleavage of N,N-Dimethylacetamide: A Unique Route to Propargylic Amines

Abstract: A copper-based system allows for the methylene insertion between an amine and a milder nucleophile, including a terminal alkyne counterpart, via C−N bond cleavage of N,Ndimethylacetamide. The method gives an expedient access to propargylic amines in good to excellent yields. A wide-ranging substrate scope and late-stage functionalization of complex molecules make the protocol practically valuable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The reaction gave convenient access to a large variety of propargylic amines in good to excellent yields (Scheme 71). 85…”
Section: Transition Metal Catalyzed Decarboxylative Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction gave convenient access to a large variety of propargylic amines in good to excellent yields (Scheme 71). 85…”
Section: Transition Metal Catalyzed Decarboxylative Transformationsmentioning
confidence: 99%
“…The reaction gave convenient access to a large variety of propargylic amines in good to excellent yields (Scheme 71). 85 It is known that the installation of a propargylic moiety can enrich the bioactivities and physicochemical properties of biologically active complex molecules, e.g. approved drugs.…”
Section: Reviewmentioning
confidence: 99%
“…A careful literature search revealed that multicomponent coupling to synthesize propargylamines could be favoured by a combination of Lewis acidity and basicity available in the designed Ag(I)metallogels. [21][22][23] Hence, we describe the application of our Ag (I)-based metallogels as a catalyst for the three-component reaction of an aldehyde, a terminal acetylene and an amine leading to propargylamines. We envisioned that our strategic incorporation of pendant -NH 2 moieties in the synthesized Ag (I)-metallogels would involve extensive counter anion-tuned hydrogen bonding to improve the interaction of the reactants and the catalyst, and assist the exchange of the proton from terminal alkynes, thereby enabling a nucleophilic alkyne attack on the in situ formed imine (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the coupling reaction of amines, haloalkanes, and alkynes (AHA coupling) was also not adapted to primary aromatic amines and diarylamines as the substrates . Recently, Bhadra and co-workers developed a novel methylene insertion strategy for propargylic amines from amines, alkynes, and N , N -dimethylacetamide; this method is highly efficient but still not suitable for primary aromatic amines and diarylamines . To date, there is only one reaction with one example of mesoporous Fe/TiO 2 nanoparticle catalyst A 3 coupling of aniline, formaldehyde, and phenylacetylene at a microwave power of 245 W (Scheme b) .…”
mentioning
confidence: 99%